Elevated allostatic load early in the course of schizophrenia. Issue 1 (December 2018) - Savransky, Anya; Chiappelli, Joshua; Fisseha, Feven; Wisner, Krista; Xiaoming, Du; Mirmomen, S.; Jones, Aaron; Adhikari, Bhim; Bruce, Heather; Rowland, Laura; Hong, L.
Abstract Stress plays a significant role in schizophrenia from disease onset to exacerbation of psychotic symptoms. Allostatic load (AL) is a measure of cumulative stress to the organism. This study is an extension of our previous work on AL and its relationship to brain structures. Here, we further determined whether elevated AL is a function of illness chronicity, or if it is already present early in the course of schizophrenia. AL was compared in schizophrenia patients early in the illness (within 5 years of disease onset), patients with chronic schizophrenia (more than 5 years of illness), and two groups of healthy controls that were age-and sex-matched to the two patient groups. This work is presented with an expanded sample and includes about two-thirds of the participants who were previously reported. We found that patients with early psychosis had significantly elevated AL score compared with their age-matched controls (p = 0.005). Chronic course patients also had elevated AL compared with age-matched controls (p = 0.003). Immune and stress hormone AL subcomponents were nominally higher in early-stage patients compared with controls (p = 0.005 and 0.04, respectively). Greater AL was also associated with more severe positive psychotic symptoms in early-stage patients (r = 0.54, p = 0.01). Elevated levels of allostatic load are already present in the early years of the schizophrenia illness, particularly in patients with more severe psychotic symptoms. AL may be a useful evaluation for the need of early intervention on psychosomatic comorbidity.